A case of a large solitary fibrous tumor arising from the retroperitoneum resected completely using an intra‐aortic balloon. Issue 10 (7th July 2022) - Tanaka, Motoki; Hirayama, Takashi; Fujihara, Risa; Fujino, Kazunari; Terao, Yasuhisa; Itakura, Atsuo
Abstract: Solitary fibrous tumors (SFTs) are rare mesenchymal cell‐derived tumors that can cause substantial bleeding during surgery due to hyper‐vascularization. We report a case of a large retroperitoneal SFT resected completely using an intra‐aortic balloon. A 71‐year‐old female with a history of type 2 diabetes mellitus presented with a tumor that was diagnosed as an insulin‐like growth factor‐II‐producing benign SFT using computed tomography‐guided biopsy. The tumor had grown from 6 to 20 cm in diameter within 4 years, with concurrent and severe hypoglycemia. Preoperative computed tomography findings showed substantial blood flow toward the tumor. The retroperitoneal tumor was observed to be widely attached. Substantial hemorrhaging during tumor resection was observed despite vascular embolism. We inflated the intra‐aortic balloon for 45 min and resected the tumor completely. In conclusion, large SFT resection requires preoperative tumor blood flow evaluation and preparation of both a vascular embolism and an intra‐aortic balloon.